(untitled) (REMUNOM, 2025)
This study aimed to review bioproduct extraction methodologies from microalgae, with a focus on sustainable alternatives and scale-up strategies for industrial applications. An integrative literature review was conducted across national and international scientific databases, focusing on publications from 2021 onward. Microalgae stand out for their high biotechnological potential, producing high-value compounds such as pigments, polyunsaturated fatty acids, and polysaccharides, and have shown feasibility in wastewater treatment processes. Among the analyzed methodologies, microwave-assisted extraction (MAE), enzyme-assisted extraction (EAE), and ultrasound-assisted extraction (UAE) were highlighted, especially when combined with green solvents, as more efficient and environmentally safe alternatives. Critical parameters influencing yield, such as liquid-to-solid ratio, temperature, power, and extraction time, were discussed. Regarding scale-up, techniques such as hydrodynamic cavitation, high-pressure microfluidization, and photobioreactor use were emphasized for their potential to optimize biomass productivity and quality. It is concluded that integrating efficient cultivation processes, intensifying extraction, and applying sustainable technologies is essential to economically enabling large-scale microalgae bioproduct production, thereby advancing the bioeconomy and circular economy.